Предмет: Алгебра,
автор: sofagureva22
a) ax-a+bx-b+cx-c
B)ax+bx-ay-by+az-bz
Приложения:
Ответы
Автор ответа:
0
a) ab+ac-b-c=a(b+c)-(b+c) = (b +c)(a -1)
b) mn-m+n-1 =m(n-1)+(n-1) = (n -1)(m +1)
в) bd-ad+3a-3b= -d(a-b)+ 3(a-b)= (a -b)(-d +3)
г) 2b-2c+ab-ac=2(b-c)+a(b-c)=(b -c)(2 +a)
a) a(x -1) +b(x -1) +c(x -1) = (x -1)(a +b +c)
b) x(a +b) -y(a +b) +z(a -b) = (a +b)(x -y) +z(a -b)
b) mn-m+n-1 =m(n-1)+(n-1) = (n -1)(m +1)
в) bd-ad+3a-3b= -d(a-b)+ 3(a-b)= (a -b)(-d +3)
г) 2b-2c+ab-ac=2(b-c)+a(b-c)=(b -c)(2 +a)
a) a(x -1) +b(x -1) +c(x -1) = (x -1)(a +b +c)
b) x(a +b) -y(a +b) +z(a -b) = (a +b)(x -y) +z(a -b)
Автор ответа:
0
http://znanija.com/task/18181289 - здорова,помоги - буду благодарен!
Похожие вопросы
Предмет: Английский язык,
автор: anastasyanikola
Предмет: Информатика,
автор: sofi711819
Предмет: Физика,
автор: galinatomisinec28
Предмет: Биология,
автор: anutkaivanova